2009
DOI: 10.1158/0008-5472.sabcs-09-6094
|View full text |Cite
|
Sign up to set email alerts
|

Final Results of a Phase II Trial Evaluating Trastuzumab and Bevacizumab as First Line Treatment of HER2-Amplified Advanced Breast Cancer.

Abstract: Background: Overexpression of HER2/neu is associated with upregulation of VEGF in human breast cancer cells in vitro. In xenograft models, superior efficacy is observed when anti-HER2 antibody trastuzumab (T) is given in combination with anti-VEGF antibody bevacizumab (B). Results from a phase I study of T + B (Breast Cancer Res Treat. 88:S124, 2004) were sufficiently positive to proceed with phase II testing. The objectives of this phase II study were to more fully determine clinical efficacy and safety of T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Preclinical data has shown that combining HER2 inhibition therapy and anti-VEGF therapy, bevacizumab, may bypass resistance to trastuzumab [32]. Clinically, two different phase II studies have shown responses in advanced HER2-postive breast cancer patients on combination trastuzumab and bevacizumab [33] and combination lapatinib and bevacizumab [34]. Phase II and III studies have also shown increased clinical efficacy of combination trastuzumab and lapatinib [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical data has shown that combining HER2 inhibition therapy and anti-VEGF therapy, bevacizumab, may bypass resistance to trastuzumab [32]. Clinically, two different phase II studies have shown responses in advanced HER2-postive breast cancer patients on combination trastuzumab and bevacizumab [33] and combination lapatinib and bevacizumab [34]. Phase II and III studies have also shown increased clinical efficacy of combination trastuzumab and lapatinib [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the combination of bevacizumab and trastuzumab has shown partial tumor regression in xenograft models (20,21). In a phase II study, bevacizumab combined with trastuzumab improved outcome in breast cancer patients with an overall response rate of 48% (22). Other promising strategies to facilitate antitumor activity include simultaneous targeting of HER2 and VEGF using a bi-specific antibody (23) or combining trastuzumab with an anti-VEGF fusion protein (24).…”
Section: Introductionmentioning
confidence: 99%
“…Results of a phase II trial evaluating trastuzumab in combination with bevacizumab, the monoclonal antibody targeting the circulating vascular endothelial growth factor (VEGF) protein, for HER2-amplified advanced breast cancer were reported by Slamon et al [18]. In this study, the combination was well tolerated and objective responses were noted in 48% of patients, with median time to progression of 9.2 months (95% CI, 5.4-20.5 months) and median OS of 43.8 months (95% CI, 40.6-NA) [19]. Another recently reported study evaluated the impact of combining two HER2 inhibitors with different targets, lapatinib and trastuzumab, compared to single agent lapatinib in patients with trastuzumabrefractory, HER2-amplified MBC [20•].…”
Section: Trastuzumabmentioning
confidence: 53%